Miller Range 07687 and its place within the CM‐CO clan. (16th September 2021) - Prestgard, Trygve; Bonal, Lydie; Eschrig, Jolantha; Gattacceca, Jérôme; Sonzogni, Corinne; Beck, Pierre
Abstract: Miller Range (MIL) 07687 is a peculiar carbonaceous chondrite officially classified as a CO3. However, it has been found to display unique petrographic properties that are atypical of this group. Moreover, Raman spectra of its polyaromatic carbonaceous matter do not reflect a structural order consistent with the metamorphic history of a type 3 chondrite. As a result, it has been suggested to be an ungrouped C2 chondrite with CO affinities, although it has not been fully excluded as a CO chondrite. The ambiguity of the meteorite's classification is the motivation behind the present study. We conclude that MIL 07687 is a unique carbonaceous chondrite with possible affinities to CO, CM, and/or some ungrouped carbonaceous chondrites. The difficulty in classifying this meteorite stems from (1) its heavily weathered nature, which interferes with the interpretation of our oxygen (O‐)isotopic measurements; (2) the overlap in the petrographic and O‐isotopic descriptions of various COs, CMs, and ungrouped meteorites in the Meteoritical Society Database. Optical and infrared spectra are consistent with the meteorite's unequilibrated nature and indicate that it is probably mildly aqueously altered. Despite traces of aqueous alteration having previously been described in MIL 07687, this is the first time that the presence of hydrated amorphous silicates is reported. In fact, our results show that its present hydration is beyond that of most CO3s, less than most CM2s, and comparable to primitive CR2s. Consequently, we support the meteorite's C2‐ung label, although a CO2 or CM2 classification cannot be fully excluded.